Robust critical values for unit root tests for series with conditional heteroscedasticity errors: An application of the simple NoVaS transformation - Panagiotis Mantalos (Cogent Economics & Finance, 2017)
In this paper, we introduce a set of critical values for unit root tests that are robust in the presence of conditional heteroscedasticity errors using the normalizing and variance-stabilizing transformation (NoVaS) and examine their properties using Monte Carlo methods. In terms of the size of the test, our analysis reveals that unit root tests with NoVaS-modified critical values have actual sizes close to the nominal size. For the power of the test, we find that unit root tests with NoVaS-modified critical values either have the same power as, or slightly better than, tests using conventional Dickey-Fuller critical values across the sample range considered.
Keywords: C01; C12; C15; 330; critical values; normalizing and variance-stabilizing transformation; unit root tests